Biomarkers For Early Alzheimer's Disease Diagnosis - Saleem, Unsa (Nepal Journal of Neuroscience, 2025)
Alzheimer's disease (AD) is a progressive neurological disorder characterized by memory loss, cognitive decline, and neurodegeneration. Early diagnosis through biomarkers is crucial for improving treatment outcomes and managing the disease. This review highlights invasive and non-invasive biomarkers for AD diagnosis which includes cerebrospinal fluid, blood-based, exosomal, and fluid-based biomarkers. Neuroimaging techniques, such as structural MRI and functional imaging, are also discussed. Recent advancements in blood-based biomarker technology and emerging AI and machine learning techniques offer promising avenues for early AD diagnosis. Future non-invasive diagnostic tools which includes wearable sensors may aid in early detection and personalized treatments.